In situ Nanostructured PVC/Silica Electrospun Membranes for Oil/Water Separation - Letícia Matos Machavelli; Sérgio H. Pezzin (Materials Research)
This study focused on the preparation of electrospun poly(vinyl chloride)/silica membranes featuring the in situ formation of modified silica nanodomains during the electrospinning process, using organosilane precursors, with the purpose to develop new adsorbents for oil-spill cleanup. The membranes were fabricated from poly(vinyl chloride) solutions in a 50/50 (v/v) tetrahydrofuran/dimethylformamide mixture, incorporating 3, 4, and 5 wt% of either (3-aminopropyl)triethoxysilane (APTS) or 3-(triethoxysilyl)propyl isocyanate (TEPI) as precursors. The resulting membranes were characterized by scanning and transmission electron microscopies, energy-dispersive X-ray spectroscopy, and differential scanning calorimetry, which confirmed the successful formation of silica nanodomains via an in situ sol-gel process during electrospinning. Additionally, contact angle measurements and oleophilic behavior were evaluated. The contact angle of the PVC membranes (136.8o) tended to decrease with the incorporation of silica nanodomains with isocyanate (126o) or amino (125.4o) groups. The membranes exhibited excellent oil sorption performance and tunable hydrophobicity, with the sample prepared with 5 wt% APTS showing the highest performance, underscoring their potential for oil/water separation applications.